2001
DOI: 10.1016/s0303-7207(00)00412-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the homologous down-regulation of transcription of the follicle-stimulating hormone receptor gene in Sertoli cells

Abstract: The action of follicle-stimulating hormone (FSH) in spermatogenesis is regulated at a fundamental level by controlling the number of competent receptors present at the surface of Sertoli cells. By controlling the number of receptors, the cell is able to modulate the timing and magnitude of subsequent signal transduction in response to FSH. One mechanism of control is the down-regulation of the steady state levels of the FSH receptor gene after exposure to FSH or agents that stimulate or prolong the cAMP signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…In previous studies of Sertoli cells, overexpression of Id2 was found to repress E-box-mediated transcription from the promoters of the FSH receptor (2,8). Together, these observations suggest that FSH-induced sequestration of E-box factors by Id2 contributes to the decreases in endogenous FSH receptor RNA observed within 6 -8 h of FSH stimulation prior to the later restoration of FSH receptor mRNA to normal levels that has been reported previously (39,40). In vivo, the levels of FSH receptor on the Sertoli cell surface rise and fall in a cyclical manner, causing related changes in cAMP levels (13,41).…”
Section: Discussionsupporting
confidence: 74%
“…In previous studies of Sertoli cells, overexpression of Id2 was found to repress E-box-mediated transcription from the promoters of the FSH receptor (2,8). Together, these observations suggest that FSH-induced sequestration of E-box factors by Id2 contributes to the decreases in endogenous FSH receptor RNA observed within 6 -8 h of FSH stimulation prior to the later restoration of FSH receptor mRNA to normal levels that has been reported previously (39,40). In vivo, the levels of FSH receptor on the Sertoli cell surface rise and fall in a cyclical manner, causing related changes in cAMP levels (13,41).…”
Section: Discussionsupporting
confidence: 74%
“…Desensitization of the FSH response in SCs involves multiple steps in signal transduction, among which the down-regulation of the transcription of the FSHR gene is of great importance (36). Previous study has shown that suppression of HADC activity by trichostatin A treatment completely prevents the homologous down-regulation of the transcription of the FSH receptor gene (26). Consistently, we have demonstrated that MTA2 represses FSH-mediated FSHR transcription by recruiting HDAC1.…”
Section: Discussionsupporting
confidence: 87%
“…The action of FSH during spermatogenesis is regulated at a fundamental level by controlling the number of competent receptors present at the surface of SCs. One mechanism of control is the down-regulation of the steady state levels of the FSHR gene after exposure to FSH by recruitment of HDAC (26). We observed that ablation of MTA2 expression significantly reversed the down-regulation of FSHR mRNA level by FSH treatment.…”
Section: Up-regulation Of Mta2 Expression By Fsh In Scs Is Mediated Vmentioning
confidence: 76%
“…Although previous studies showed that SF-1 might contribute to cell-specific activity of mouse FSHR promoter [9], SF-1 alone may not be the sole mediator governing a Sertoli or granulosa cell-specific expression [19,47]. Additional elements and factors must synergize or antagonize SF-1 to direct the expression in a developmental manner [11,12,16]. In the present study, we showed that three activators of USF, AP-1, and SF-1 bound a composite ciselement (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different cellular combinations of transcription factors interact with the same promoter regions, leading to the type-specific transcription in the cells. Moreover, RNA processing and posttranslational modification also determine the functional protein levels of FSHR on the cell membrane [15,16]. Although some of the mechanisms by which the FSHR gene is down-regulated by FSH stimulation and protein kinase A signal transduction pathway have recently been proposed, little detailed information has been reported so far regarding the factors that lead to suppression of the FSHR gene [11,16].…”
Section: Introductionmentioning
confidence: 99%